Prevalence of dry eye in college students at Uparwara community in Raipur - Kolla, Andrea; Dahariya, Devesh; Ram, Male Shiva; Kolla, Varaprasad (International Journal Of Community Medicine And Public Health, 2019)
Background: The study aims to investigate the prevalence of dry eye in college students in the Uparwara community. Methods: This pilot study was conducted tenure to declaration of Helsinki rules with n=240 (males 200 and females 40) with in the age group of 18-25 years, OSDI questionnaire was used to assess the prevalence among the college students of Uparwara community at Raipur. Results: Data from 240 subjects were analyzed with a mean age group of 19.41±0.70 mean±SD. This OSDI questionnaire study with subscales for dry eye symptoms were measured in both the genders males 213 (89%), females 27 (11%). The percentage distributions among the subjects showed that 116 (48.3%) participants reported dry eye symptoms and 124 (51.6%) was normal. Conclusions: This study emphasized on the prolonged usage of VDT and electronic devices i.e., >4 hours as a compliance factor for dry eye, our data suggest that VDT usage less than 4 hours also can be a risk factor for dry eye since all our 116 participants with dry eye symptoms are VDT users and interestingly 78% (90) of them are <4 hours VDT users but still have dry eye symptoms.